ATTITUDE REALIZATION IN NEWS REPORTS: AN INTERPRETATION THROUGH AN APPRAISAL ANALYSIS - Asad, Saira; Noor, Siti Noor Fazelah Binti Mohd; Indah, Rohmani Nur; Jaes, Lutfan Bin (Universitas Pendidikan Indonesia, 2021)
For the maintenance of the authorial voice, newspapers use rhetorical markers as an external supporting voice to win their readership. The current five-year studies show that news writers maintain engagement with their readers by their stances towards their point of views. This study aimed to find the attitudinal stances of two Pakistani Online newspapers i.e. ‘Dawn’ (alternative newspaper) and ‘The News’ (mainstream newspaper). The newspaper’s inclination was identified through its language. To discover the newspapers’ stances, Martin and White (2005) ‘Appraisal Analysis’ framework was employed on ‘2’ news reports comprising of ‘5013’ words on Prime Minister Imran Khan’s Speech at 74th United Nations’ session along with Critical Discourse Analysis (CDA) by Norman Fairclough (1995). It was found that both newspapers indirectly invoked attitudes by laying evaluative ground which was explicitly explained in the quoted text. The prime minister of Pakistan Imran Khan was found the ‘Appraiser’ in both news reports and served as a main social actor in highlighting Pakistan’s current issues. The issues are expected to be solved urgently for peace and prosperity in the region by the involvement of world leaders and United Nations on Kashmir conflict between Pakistan and India, climate change and elimination of Islam phobia.